Evaluación de la aplicación de tratamientos odontológicos preventivos, UNACH 2019 - Bárbara Cristina, Espín Viera (2021)
ABSTRACT This research focused on evaluating the effectiveness of the application of pits and fissure sealants placed in an oral health promotion and prevention program at the National University of Chimborazo. A descriptive, cross-sectional, observational study carried out it. Observation applied as data collection techniques and clinical history and a sealant evaluation record sheet used as instruments, from which the necessary data obtained to respond to the objectives set. The study population delimited by 130 pediatric patients from the Javier Saenz Educational Unit, aged between 6 and 12 years, from which a sample of 109 patients selected under inclusion and exclusion criteria taken. The results indicated that the application of sealants with ART and adhesive techniques is an undeniably effective preventive treatment, however, the superiority of one of the materials previously evaluated could be observed, in the study a direct association determined between the state of the sealant and the applied technique (p = 0.14) and the non-association between the presence or absence of caries and the applied technique determined (p = 0.68). With these data it was possible to determine the importance of its application and above all of a continuous control of the treatment in order to guarantee successful results with longer retention time in the tooth and fulfilling its preventive function of dental caries. Keywords: Sealants, Pediatric dentistry, Preventive treatment, Retention, Dental caries. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324